1988
DOI: 10.2172/137492
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and speciation studies of waste radionuclides pertinent to geologic disposal at Yucca Mountain: Results on neptunium, plutonium and americium in J-13 groundwater; Letter report (R707): Reporting period, October 1, 1985--September 30, 1987

Abstract: SummaryWe have studied the solubilities of neptunium, plutonium, and americium in J-13 groundwater from Yucca mountain (Nevada) at three temperatures and hydrogen ion concentrations. They are 25°, 60°C, and 90°C and pH 5.9, 7.0, and 8.5. Tables I, II, and III summarize the results for neptunium, plutonium, and americium, respectively.The results for 25°C are from a study which we did during FY 1984. We included these previous results in the tables to give more information on the solubility tempera ture dependa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A number of studies have shown Pu(VI) carbonate complexes to be stable and potentially mobile species [2][3][4][5][6]. The Pu(VI) carbonate system has been examined and characterized by a number of methods; UV-Visible spectroscopy [7][8][9][10][11][12][13][14][15], "C NMR spectroscopy [16,17], Raman spectroscopy [10,18], X-ray diffraction [14,19], and solubility experiments [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown Pu(VI) carbonate complexes to be stable and potentially mobile species [2][3][4][5][6]. The Pu(VI) carbonate system has been examined and characterized by a number of methods; UV-Visible spectroscopy [7][8][9][10][11][12][13][14][15], "C NMR spectroscopy [16,17], Raman spectroscopy [10,18], X-ray diffraction [14,19], and solubility experiments [19,20].…”
Section: Introductionmentioning
confidence: 99%